Fatigue induced changes in conical implant–abutment connections. Issue 11 (November 2015) - Blum, Kai; Wiest, Wolfram; Fella, Christian; Balles, Andreas; Dittmann, Jonas; Rack, Alexander; Maier, Dominik; Thomann, Ralf; Spies, Benedikt Christopher; Kohal, Ralf Joachim; Zabler, Simon; Nelson, Katja
Highlights: Synchrotron Radiation. Visualization of micromotion in implant–abutment connection. Abstract: Objectives: Based on the current lack of data and understanding of the wear behavior of dental two-piece implants, this study aims for evaluating the microgap formation and wear pattern of different implants in the course of cyclic loading. Methods: Several implant systems with different conical implant–abutment interfaces were purchased. The implants were first evaluated using synchrotron X-ray high-resolution radiography (SRX) and scanning electron microscopy (SEM). The implant–abutment assemblies were then subjected to cyclic loading at 98 N and their microgap was evaluated after 100, 000, 200, 000 and 1 million cycles using SRX, synchrotron micro-tomography (μCT). Wear mechanisms of the implant–abutment connection (IAC) after 200, 000 cycles and 1 million cycles were further characterized using SEM. Results: All implants exhibit a microgap between the implant and abutment prior to loading. The gap size increased with cyclic loading with its changes being significantly higher within the first 200, 000 cycles. Wear was seen in all implants regardless of their interface design. The wear pattern comprised adhesive wear and fretting. Wear behavior changed when a different mounting medium was used (brass vs. polymer). Significance: A micromotion of the abutment during cyclic loading can induce wear and wear particles in conical dental implant systems. This feature accompanied with the formation of a microgap at the IAC is highly relevant for the longevity of the implants.